The temporal and spatial variation characteristics of bacterial communities in Zhangjiayan reservoir sediments and their response mechanisms to environmental factors - Li, Yong; Li, Yajie; Yu, Xintao; Gong, Sidan; Du, Jiankun; Wang, Jianping (Frontiers in Environmental Science, 2025)
After exogenous pollutants in Zhangjiayan Reservoir were effectively controlled, sediment phosphorus release became a key driver of eutrophication. Thus, exploring how sediment bacterial communities respond to environmental factors and phosphorus cycling is important. In this study, we collected Zhangjiayan sediment and overlying water samples in spring (April), summer (July), fall (November), and winter (January) from 2022–2023, measured their physical and chemical factors as well as amplified and sequenced 16S rRNA genes of the sediment samples using Illumina MiSeq high-throughput sequencing technology to study the spatial and temporal variations of the bacterial community in the reservoir sediments. The results showed that the sediment was rich in bacterial diversity: a total of 63 phyla, 192 classes, 459 orders, 761 families, and 1,485 genera of the bacterial domain were detected in the sediment samples from Zhangjiayan Reservoir, with Proteobacteria and Actinobacteria as the dominant phyla. The bacterial communities exhibited significantly distinct clustering patterns between spring/summer and autumn/winter seasons (P < 0.05), with both diversity indices and taxonomic abundance being markedly higher during spring and summer compared to autumn and winter periods. In terms of community structure, the spring and summer samples showed more concentrated clustering characteristics, whereas the fall and winter samples showed a significantly dispersed distribution pattern. DO and SRP in the overlying water, as well as pH, phosphorus, ALP and TOC of the sediments were the key influencing factors for the differences in bacterial community structure. The relative abundance of the dominant genera norank_f_Anaerolineaceae and Dechloromonas was significantly and positively correlated with SRP content (P < 0.01). The relative abundance of hgcI_clade was highly significantly negatively correlated with SRP content (P < 0.01). The average clustering coefficient and modularity coefficient of the co-occurrence network of bacterial communities in sediments were at a high level, characterized by significant seasonal variations, and significantly positively correlated with dissolved reactive phosphorus (SRP) concentration (P < 0.01). These results enhance our understanding of bacterial community structure, composition, distribution, and their roles in phosphorus cycling in Southwest China’s sub-deep lake reservoirs, providing valuable insights for eutrophication treatment and aquatic ecosystem protection.